THE ANALYSIS OF THE AUTHORITY OF THE CORRUPTION ERADICATION COMMISSION IN CONDUCTING STING OPERATIONS - Ahmad Faiz Alamsyah; Ayu Widia Pertiwi (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The state suffers losses as a result of corrupt practices. The general populace shares the state's concern over this crime. The state and public are experiencing instability, and the Corruption Eradication Commission's position and power are crucial in overcoming and minimizing this. So, a sting operation is one of the things the Corruption Eradication Commission does. In this instance, it's important to consider not just the procedures followed by the Corruption Eradication Commission during sting operations, but also the operation's legal foundation and any elements that may have impeded its success. Opponents of the OTT point out that the Criminal Procedure Code only uses the phrase